Recent advances in gradient biomimetic scaffolds for tendon-bone interface regeneration - Xie, Xianyan; Wang, Yu; Li, Ziyan; Yang, Gaoyuan; Cheng, Guodong; Qin, Shuqi; Wang, Huiguo; Zhu, Lin (Frontiers in Bioengineering and Biotechnology, 2025)
Injury and repair of the tendon-bone interface (TBI) pose a significant challenge in the fields of orthopedics and sports medicine. Due to the gradients in structure, composition, mechanical properties, and biological signals across the TBI, transitioning from flexible tendon to rigid bone, traditional surgical approaches often struggle to reconstruct its functional structure, leading to poor mechanical properties of the interface after repair and high re-tear rates. In contrast, gradient biomimetic scaffolds, by mimicking the continuous gradients of native TBI, offer an effective solution for achieving functional TBI regeneration. This review systematically summarizes the research progress of gradient biomimetic scaffolds for TBI regeneration in recent years. Firstly, we discuss the fine structure, physiological functions of native TBI, and the repair challenges faced after its injury, emphasizing the necessity of reconstructing gradient structures. Subsequently, it focuses on the design principles and core biomimetic strategies of gradient biomimetic scaffolds, discussing in depth the principles of construction and implementation strategies for physical structure gradients (e.g., porosity, fiber orientation, mechanical modulus), chemical composition gradients (e.g., degree of mineralization, polymer/ECM components), and biological signal gradients (e.g., growth factors, genes). Building upon this, this review comprehensively reviews various biomaterials for gradient scaffold construction, including natural polymers (collagen, silk fibroin, chitosan, etc.), synthetic polymers (PCL, PLGA, PU, etc.), and inorganic bioactive materials (calcium phosphate ceramics, bioactive glass), analyzing their characteristics, functionalization methods, and applications in gradient construction. Furthermore, this review also systematically summarizes and compares major fabrication techniques for gradient biomimetic scaffolds, particularly the advantages and limitations of electrospinning and additive manufacturing (3D printing) in constructing specific gradient features, and highlights emerging techniques such as microfluidics. Finally, building upon the summarized existing research findings, this review critically analyzes the key challenges and technical bottlenecks currently facing gradient biomimetic scaffolds regarding structural biomimetic accuracy, spatio-temporal control of biological functions, vascularization, and immunocompatibility, and offers perspectives on future research directions, such as smart scaffolds, integration of multiple gradients, personalized manufacturing, and clinical translation strategies.